2019
DOI: 10.2147/ott.s194463
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long noncoding RNA STXBP5-AS1 inhibits cell proliferation, migration, and invasion through inhibiting the PI3K/AKT signaling pathway in gastric cancer cells</p>

Abstract: Poor prognosis of gastric cancer (GC) has partly been a result of late diagnosis due to nonspecific symptoms in the early stages. The overall survival rate of patients with GC is quite low. Here, we presented the functional role and potential mechanism of long noncoding RNA STXBP5-AS1 in GC. Materials and methods: CCK-8, scratch wound healing and Transwell assays were conducted to analyze proliferation, migration, and invasion of SGC7901 and MKN45 cells. Real-time polymerase chain reaction (qPCR) and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…GDC-0068 To evaluate the efficacy of GDC-0068 in combination with oxaliplatin, 5-fluorouracil, and leucovorin chemotherapy in participants with advanced or metastatic GC or GEJC II NCT01896531 To study the side effects and BD of MK2206 and lapatinib ditosylate when given together with trastuzumab in treating patients with locally advanced or metastatic HER2 + BC that cannot be removed by surgery I NCT01705340 [109][110][111][112][113][114][115][116][117][118][119][120][121][122]. A lot of clinical trials of PI3K inhibitors (BKM120, BYL719 and GSK2636771.…”
Section: Nct02240212mentioning
confidence: 99%
“…GDC-0068 To evaluate the efficacy of GDC-0068 in combination with oxaliplatin, 5-fluorouracil, and leucovorin chemotherapy in participants with advanced or metastatic GC or GEJC II NCT01896531 To study the side effects and BD of MK2206 and lapatinib ditosylate when given together with trastuzumab in treating patients with locally advanced or metastatic HER2 + BC that cannot be removed by surgery I NCT01705340 [109][110][111][112][113][114][115][116][117][118][119][120][121][122]. A lot of clinical trials of PI3K inhibitors (BKM120, BYL719 and GSK2636771.…”
Section: Nct02240212mentioning
confidence: 99%
“…10 Aberrant downregulation of lncRNA STXBP5-AS1 in gastric cancer leads to accelerated growth and enhanced metastasis of tumor cells through activation of PI3K/AKT signal. 11 Due to their important roles, several lncRNAs may be effective biomarkers for diagnosis or prognosis in cancer. 12,13 LINC00665 has been reported to promote progression of several cancers, including lung cancer, gastric cancer and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…AKT protein kinase has been widely studied as a cancer-promoting factor. A recent study reported that lncRNA STXBP5-AS1 can inhibit the activation of AKT in GC, which leads to the inhibition of proliferation and migration of GC cells (38).…”
Section: Discussionmentioning
confidence: 99%